International Student Engagement: An Exploration of Student and Faculty Perceptions - Wang, Rong; BrckaLorenz, Allison (Journal of International Students, 2018)
An increasing number of faculty have brought up questions and concerns comparative studyabout supporting international students’ academic engagement and success. However, little is known about faculty’s approaches to international student engagement and how they may differ from international students’ selfreported engagement at four-year institutions. Using data from the National Survey of Student Engagement and Faculty Survey of Student Engagement, both large-scale and multi-institutional datasets, this study explores international student engagement in learning strategies, collaborative learning, and student-faculty interaction as well as international student engagement from the perspectives of faculty and students. Recommendations on supporting international student engagement from an individual faculty level, department level, and institutional level are discussed.